2017
DOI: 10.3892/ol.2017.6648
|View full text |Cite
|
Sign up to set email alerts
|

RAS protein activator-like 1 is functionally involved in hypoxia resistance in breast cancer cells by targeting hypoxia inducible factor-1α

Abstract: RAS protein activator-like 1 (RASAL1) is a member of the RAS GTPase-activating protein family, and previous studies indicate that RASAL1 is involved in the progression of hypoxia resistance in breast cancer cells. In the present study, increased levels of hypoxia inducible factor-1α (HIF-1α) were observed to be accompanied with increased expression of RASAL1 in the breast cancer cell lines MCF-7 and MDA-MB-231 cells under hypoxia. Based on this, it was postulated that RASAL1 may serve a functional role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In particular, RASAL1 overexpression resulted significantly correlated with a worse outcome (increased death) in endometrial cancer ( Figure S1D ), whereas NPL overexpression was correlated to a worse outcome in liver and renal cancers ( Figure S1E ). However, in other studies RASAL1 was found significantly downregulated in cancer [ 19 , 20 ], whereas its overexpression blocked cancer progression [ 21 ].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In particular, RASAL1 overexpression resulted significantly correlated with a worse outcome (increased death) in endometrial cancer ( Figure S1D ), whereas NPL overexpression was correlated to a worse outcome in liver and renal cancers ( Figure S1E ). However, in other studies RASAL1 was found significantly downregulated in cancer [ 19 , 20 ], whereas its overexpression blocked cancer progression [ 21 ].…”
Section: Resultsmentioning
confidence: 95%
“…POLN encodes for the DNA Polymerase nu involved in cross-link repair, homologous recombination and binding to BRCA1 [ 36 ]. ROS1 and RASAL1 are two genes with established roles in tumor development and progression in different types of cancer [ 21 , 24 , 25 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RAS protein activator 1 (RASAL1) protein is known to be involved in the progression of hypoxia resistance in breast cancer cells. The increase of intracellular Ca 2+ ions stimulates RASAL1, which leads to attenuation of RAS activation and mitogen-activated protein kinase (MAPK) activity and contributes to tumor progression through weakened anti-RAS activity [12] . In periods of hypoxia, reactive oxygen species accumulation activates PI3k/Akt (Protein-kinase B) and MAPK/ERK (extracellular signal-regulated kinase) pathways, essential for the maintenance of carcinogenesis, tumor angiogenesis and activation of HIF-1α.…”
Section: Hif-1α Modulation Under Hypoxiamentioning
confidence: 99%